Improving Medication‐Related Outcomes in Chronic Liver Disease - Kelly L. Hayward; Rianne A. Weersink (Hepatology Communications, 2020)
Patients with chronic liver disease (CLD) are becoming increasingly complex due to the rising prevalence of multimorbidity and polypharmacy. Medications are often essential to manage the underlying liver disease, complications of cirrhosis and portal hypertension, and comorbidities. However, medication‐related problems (MRPs) have been associated with adverse patient outcomes, including hospitalization and mortality. Factors that can contribute to MRPs in people with CLD are variable and often entwined. This narrative literature review discusses key barriers and opportunities to modify risk factors and improve medication‐related outcomes for people with CLD.